Post-treatment PET/CT and p16 status for predicting treatment outcomes in locally advanced head and neck cancer after definitive radiation. - Awan, Musaddiq; Lavertu, Pierre; Zender, Chad; Rezaee, Rod; Fowler, Nicole; Karapetyan, Lilit; Gibson, Michael; Wasman, Jay; Faulhaber, Peter; Machtay, Mitchell; Yao, Min (European Journal of Nuclear Medicine & Molecular Imaging, 2017)
Purpose: To retrospectively review post-treatment (post-tx) FDG-PET/CT scans in patients with advanced head and neck squamous cell carcinoma (HNSCC) and known p16 status, treated with definitive (chemo)radiation (RT). Methods: A total of 108 eligible patients had N2A or greater HNSCC treated with chemoRT from August 1, 2008, to February 28, 2015, with post-tx PET/CT within 6 months after RT. Kaplan-Meier curves, log-rank statistics, and Cox proportional hazards regression were used for statistical analysis. Results: Median follow-up was 2.38 years. Sixty-eight (63.0%) patients had p16+ and 40 (37.0%) had p16− status. Two-year overall survival and recurrence-free survival were 93.4% and 77.8%, respectively. The negative predictive value (NPV) of PET/CT for local recurrence (LR) was 100%. The NPV for regional recurrence (RR) was 96.5% for all patients, 100% for p16+ patients, and 88.5% for p16− patients. The positive predictive value (PPV) of PET/CT for recurrence was 77.3% for all patients, 50.0% for p16+, and 78.6% for p16−. The PPV for LR was 72.7% for all patients, 50.0% for p16+ patients, and 72.7% for p16− patients. The PPV for RR was 50.0% for all patients, 33% for p16+, and 66.6% for p16−. Post-tx PET/CT and p16 status were independent predictors of recurrence-free survival ( p < 0.01). Conclusions: Post-tx PET/CT predicts treatment outcomes in both p16 + and p16− patients, and does so independently of p16 status. P16− patients with negative PET have a 10% risk of nodal recurrence, and closer follow-up in these patients is warranted.